Implications Organisationnelles Et Humaines De L’introduction Des Tic Pour La Frh : -Cas De L’administration Publique Marocaine- - Obada, Meriem (European Scientific Journal, ESJ, 2017)
In this study we are interested in the organizational and human implications of ICTs especially for HRF as we see them as more crucial to the effectiveness of the organization as a whole. Mobilizing a contextualist approach, our contribution consists in reconsidering the field of study in order to integrate public administrations, which, like private companies, are strongly challenged by requirements of efficiency and effectiveness. We opted for a quantitative approach by administering a questionnaire to HR managers in about 40 public administrations and used various documents to enrich and complete the field study. The introduction of ICT in public administration has led to a reorganization of work and a change in working conditions, so the HRF becomes more flexible and communicative. However, interactive services and activities that contribute to skills development are scarce. An ICT culture based on the ethical sense and the mobilization of all the stakeholders is necessary for a complete success of the computerization project of the Public Administration.